Genderinequalities in overweight and obesity Among indigenous Maya Chontales of Tabasco, Mexico - Cruz Sánchez, Marcelina (2012)
Obesity has become a global epidemic with women registering higher rates than men. It is unknown why this phenonmenon occurs or whether it acquires specific characteristics among indigenous populations. Objective: To identifiy gender inequalities that underly excess body weight and obesity among the indigenous Maya Chontales of Tabasco. Materials and Methods: Qualitative study of 15 in-depth interviews of Chontal men and women. Interview themes included categories of lifestyle, ethnicity, customs and eating habits, uses and significance of the body, and gender norms. The interviews were recorded and transcribed. Written informed consent for participation in the study, was well as ethics committee approval, were obtained. Results: Women tend to excess body weight and obesisty to a greater extent than men. Physical exercise is forbidden to women as public spaces for sports are exclusively male domains. After maternity, it is generally assumned that it is ?normal? to be overweight. Obesity is considered an unavoidable genetic heritage, not a disease and weight loss is undesirable at any stage of life. Conclusions: Gender inequalities are an important conditioning factor in excess weight and obesity among Chontal women. The results of this study have implications for the promotion of healthy lifestyles for reducing rates of excess weight and obesity in indigenous populations, particularly among women.